Exploratory Study Of Impact Of Learning And Development On Employee Behaviour And Retention In Small And Medium IT Enterprises In India - Dubey, Pooja Yamunaprasad (Digital Repository of Theses, 2025)
Attrition is a major issue that affects the performance of IT companies negatively. Past literature has revealed strong associations between L&D & employee attrition. Thus, it is used as one of the retention methodologies by many large IT enterprises across the globe. However, this practice is nearly non-existent in SMEs. This study proposes the adoption of L&D in Indian IT SMEs by demonstrating the impact of learning and development (L&D) on employee behaviour in Indian IT SMEs. It uses triangulation for an investigation that includes interviews, learning intervention impact analysis, and focus group discussions as primary methods.